Renal-limited lupus-like glomerulonephritis - Noemi Esparza Martín; Rita Guerra Rodríguez; Ernesto Fernández Tagarro; Santiago Suria González; César García Cantón (Archives of Renal Diseases and Management - Peertechz Publications, 2017)
In  the  setting  of  an  IgG-dominant  immune  complex-mediated  glomerulonephritis,  there  are  multiple  pathological fi ndings that strongly suggest the diagnosis of lupus nephritis (LN) including "full-house" immunofluorescence staining for IgG,  IgM,  IgA,  C3  and  C1,  extraglomerular  immune  deposits,  combined mesangial, subendothelial and subepithelial immune deposits   and   the   presence   of   endothelial   tubuloreticular   inclusions (TRI). If at the time of biopsy or during the period of follow-up, the patient displayed no extrarenal manifestations or  serological  evidence  of  systemic  lupus erythematosus  (SLE)  it  is  denominate  renal-limited  lupus-like  glomerulonephritis  (RLLN) and there are reports both adults and children. Purpose of  the  study:  Clinical  features  review  of  in  the  peer-reviewed academic literature. Results Clinical features   RLLN  patients  were more  often  male  and  they  presented  with  lower-range  erythrocyturia,  more  proteinuria and less complement consumption in the classical  pathway  than  LN  patients.